A preliminary study on semen collection, its evaluation, and testicular and sperm morphometries in the wild proboscis monkey (Nasalis Larvatus) - Zainuddin, Zainal Zahari; Mohamed Tarmizi, Mohamed Reza; Yap, Chee Keng; Erut, Alvin; Wan Jaafar, Wan Nor Fitri; Salleh, Annas (Danishgah-i Tihran, danishkadah-i dampizishki, 2021)
Introduction: The proboscis monkey (Nasalis larvatus) is an endangered species with a declining population. This article describes the first successful attempt at sperm collection and evaluation, and the testicular and sperm morphometries of the wild proboscis monkey in Sabah, Malaysia. Material and methods: Eight semen collection procedures using electro-ejaculation and digital manipulation were conducted in three wild adult male proboscis monkeys. A total of 21 ejaculates were collected. The testicular biometry was measured with the aid of ultrasonography. Sample evaluation included semen volume and pH and sperm concentration, viability, and abnormality. The sperm morphometry was undertaken using phase contrast microscopy. Results: The mean (±SD) total testicular volume of these animals was 5.77 cm3 (±1.58). Semen collection by electro-ejaculation resulted in an 84% success rate, while digital manipulation did not result in any ejaculation. Each animal showed different semen characteristics, where the volume was 5-540 μL, pH 8-9, and sperm concentration 0.041-83.00 ×106/mL. The percentage of abnormal sperm was high at 76.8% (±89.60), largely due to midpiece abnormality. Normal sperm had a spherical head and long tail with a head : midpiece : tail length ratio of 1 : 2: 8. Conclusion: The social status of these animals may contribute to the generally low quality of the semen. The techniques and data from this study are useful for future conservation and application of assisted reproductive technology in this species.